La problematicidad de la reflexión anticipada en la Lógica de Jena: de la metacategoría de la Infinitud a la fundación de la Relación (Revista Eletrônica Estudos Hegelianos, 2019)
This article will discuss some fundamental points of Jena’s Logic of 1804/05, particularly the moment of Infinity and its transition to Relation. In these pages, some key points are present for the development of Hegelian logic and, more generally, for its philosophical system. From this text, I will analyze the relationship between logic and metaphysics; I will concentrate on the transformation of dialectics and reflection, in a speculative and systematic sense. In this sense, it is important to see the change of meaning that skepticism has for Hegel during those years. We will concentrate on the anticipiert Reflection (anticipated reflection) that will not give completely satisfactory results, at least in the Logic of 1804/05. The article does not offer a solution to the systematic question of this Hegelian manuscript, but tries to analyze it in its most fundamental problems: the role of dialectics, the evolution of reflection and the relationship between subjectivity and objectivity in this first system.